ANALISIS PERLINDUNGAN HUKUM TERHADAP NASABAH PENGGUNA INTERNET BANKING PADA BANK BRI - Ratuloli, Samson; Nubatonis, Orpa J; Dinata, Husni Kusuma (Petitum Law Journal, 2025)
This research aims to analyze the legal protection for customers using internet banking services at Bank BRI in Indonesia. This topic is important because, to date, there are no specific regulations that explicitly govern the rights of internet banking users. This research focuses on two main questions: how legal protection is provided to internet banking customers at Bank BRI, and what challenges are encountered in the implementation of such legal protection. The research method used is normative, with a legislative approach to relevant laws and regulations, such as Law No. 10 of 1998 on Banking, Law No. 8 of 1999 on Consumer Protection, as well as regulations from the Financial Services Authority (OJK) and Bank Indonesia, which govern customer data security and digital banking services. The research results show that Bank BRI has implemented preventive legal protection measures, such as security policies, customer education, and security technologies like Secure Socket Layer (SSL). However, significant challenges in providing legal protection to customers include the complexity of regulations related to cybercrime and the lack of law enforcement that adapts to new technological developments, such as artificial intelligence (AI) and blockchain. Cross-border jurisdiction also becomes an obstacle in handling cybercrime cases. Additionally, the lack of customer education on cybersecurity increases the risk of attacks, while cyber threats continue to evolve with increasingly sophisticated methods. This research is expected to contribute to the development of more effective legal protection regulations for internet banking customers.